Japanese Language Development for Tokutei Ginou Candidates Through the GROW-ME Coaching Model - Chornelly Aror, Susanti; Sambe, Nozomi; Bintang Pratiwi Harahap, Putri (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: This study aimed to evaluate the effectiveness of the GROW-ME (Goal-Reality-Options-Will-Metacognitive Enhancement) training model in enhancing Japanese language proficiency, motivation, and self-efficacy among prospective Tokutei Ginou program participants, compared to traditional instruction methods. A quasi-experimental design with pre-test and post-test control groups was employed over 12 weeks. Fifty participants were randomly assigned to experimental (n=25) and control (n=25) groups. The experimental group achieved significantly higher Japanese proficiency scores (258.4±32.1) compared to controls (189.6±28.7; p<0.001, Cohen's d=2.31). All skill components showed significant improvements: listening (68.2 vs 52.8), reading (65.8 vs 48.1), grammar (62.4 vs 45.2), and vocabulary (62.0 vs 43.5), all p<0.001. Motivation increased from 5.2 to 6.1 in the experimental group versus 5.1 to 5.3 in controls (p=0.001). Self-efficacy improved substantially from 4.1 to 5.8 versus 4.0 to 4.4 (p<0.001). Growth curve modeling revealed 9.4 points per week improvement in the experimental group compared to 3.9 points per week in controls. JLPT N4 achievement rates were 84% versus 32% respectively.This study is the first to demonstrate the effectiveness of an integrated coaching-based model (GROW-ME) combining metacognitive enhancement and cultural competency training for Japanese language acquisition in the Tokutei Ginou context. With extraordinarily large effect sizes (Cohen's d>2.0) rarely observed in educational research, the findings establish that structured metacognitive development alongside language instruction produces superior outcomes compared to traditional methods. The model demonstrates a dual impact on both cognitive domains (language proficiency) and affective domains (motivation, self-efficacy), coupled with exceptional JLPT N4 achievement rates. This represents a paradigm shift in preparing foreign workers for Japanese employment contexts.